Group discussions and test-enhanced learning: individual learning outcomes and personality characteristics. Issue 2 (7th February 2017) - Stenlund, Tova; Jönsson, Fredrik U.; Jonsson, Bert
ABSTRACT: This paper focuses on the factors that are likely to play a role in individual learning outcomes from group discussions, and it includes a comparison featuring test-enhanced learning. A between-groups design ( N = 98) was used to examine the learning effects of feedback if provided to discussion groups, and to examine whether group discussions benefit learning when compared to test-enhanced learning over time. The results showed that feedback does not seem to have any effect if provided to a discussion group, and that test-enhanced learning leads to better learning than the discussion groups, independent of retention interval. Moreover, we examined whether memory and learning might be influenced by the participants' need for cognition (NFC). The results showed that those scoring high on NFC remembered more than those who scored low. To conclude, testing trumps discussion groups from a learning perspective, and the discussion groups were also the least beneficial learning context for those scoring low on NFC.